ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI KERJA PENDUDUK LANJUT USIA DI KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Setia Rahini, Ni Luh Putu; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
This research aims to analyze the effect of marital status, education level, health of the elderly, status of the head of the family, old age allowance, family income, and the number of dependents simultaneously and partially, and to find out whether the number of dependents plays a role in moderating the effect of family income in Abiansemal District, Kabupaten Badung. The population in this study was 14,430 people aged 60 and over using the non-probability sampling method combining the purposive sampling method and the accidental sampling method and obtained a sample of 123 respondents. Collection methods in the form of observation, structured interviews, and in-depth interviews. The data analysis technique used is descriptive analysis and Moderated Regression Analysis (MRA). Based on the results of the analysis, it is known that the variables simultaneously influence the work participation of the elderly population. Health of the elderly and the number of dependents have a positive effect, education level and family income have a negative effect, the status of the head of the family has a higher effect, marital status and old-age benefits have a partially lower effect, and the number of dependents plays a role in strengthening the influence of family income on the work participation of the elderly age in Abiansemal District, Badung Regency.